The clinical and epidemiological risk factors of infections due to multi-drug resistant bacteria in an adult intensive care unit of University Hospital Center in Marrakesh-Morocco - Adel El mekes; Kawtar Zahlane; Loubna Ait said; Ahmed Tadlaoui Ouafi; Mustapha Barakate (Elsevier, 2020)
Background: Intensive care units (ICUs) are considered epicenters of antibiotic resistance. The aim of this study is to determine clinical risk factors, epidemiology and the causative agents of multi-drug resistant bacteria in the ICU of the University Hospital in Marrakesh-Morocco. Methods: A one year case control study was carried out in our 10-bed clinical and surgical ICU from March 2015 to March 2016. The epidemiological surveillance was done by collecting data in the medical records with the help of a questionnaire. The antibiotic susceptibility testing was used following the recommendations of the Antibiogram Committee of the French Society of Microbiology and the European Committee for Antimicrobial Susceptibility Testing, 2015. Results: Among the 479 admitted patients, 305 bacteria were isolated and identified as Acinetobacter baumannii (31%), Enterobactereacae species (30%), and Staphylococcus (24%), P. aeruginosa (10%) and other bacterial strains (5%). The rate of MDR bacteria acquisition was 41% (124/305) with domination of A. baumannii resistant to imipenem (70%) and followed by Extended Spectrum β-lactamases producing Enterobacteriaceae, P. aeruginosa resistant to Ceftazidime, and Methicillin-resistant S. aureus (18%, 7%, and 5% respectively). The distribution of the common nosocomial infections were dominated by pneumonia, bacteremia, and catheter-related blood stream infections (39%, 29%, and 17%) respectively. Multivariate analysis identified lack of patient isolation precautions (OR: 7.500), use of quadri or triple therapy (OR: 5.596; OR: 5.175), and mechanical ventilation (OR: 4.926), as the most significant clinical and epidemiological factors associated with acquisition of MDR bacteria. The attributable mortality, in this ICU, of patients with MDR bacteria, is about 12%. Conclusions: The incidence of MDR was higher compared with that of developed countries. The implementation of standard infection control protocols, active surveillance of MDR and generation of data on etiological agents and their antimicrobial susceptibility patterns are urgently needed in our hospital. Keywords: Epidemiology, Risk factor, Antibiotic resistance, Nosocomial infection, Morocco